Budaya Saprahan Melayu Sambas: Asal Usul, Prosesi, Properti dan Pendidikan Akhlak - Wahab Wahab; Erwin Erwin; Nopi Purwanti (Arfannur, 2020)
Sambas inherited a rich cultural treasure which is one of the richest in West Kalimantan. One such legacy is the Saprahan tradition. This article aims to reveal the origin, property, procession, and moral education contained in this tradition. This paper uses literature review and interviews as support. The data analysis technique uses content analysis. This study concludes that the saparah tradition has been detected since the days of the Sambas kingdom turning into Islamic power, the properties and processions of saprahan symbolizing the value of religious teachings in the form of the pillars of Islamic teachings. Meanwhile, the moral education contained in it is mutual cooperation (ta'awun), respect for guests (ikram dhuyuf), and togetherness (ma'iyah). Sambas mewarisi kekayaan khazanah budaya yang merupakan salah satu terkaya di Kalimantan Barat. Salah satu peninggalan tersebut adalah tradisi Saprahan. Artikel ini bertujuan untuk mengungkap asal usul, properti, prosesi, dan pendidikan akhlak yang terdapat dalam tradisi ini. Tulisan ini menggunakan kajian pustaka dan wawancara sebagai pendukung. Teknik analisis datanya menggunakan content analysis. Kajian ini menyimpulkan bahwa tradisi saparah dideteksi telah ada sejak zaman kerajaan Sambas beralih menjadi kuasa Islam, properti dan prosesi saprahan melambangkan nilai ajaran agama berupa pilar- pilar ajaran Islam. Sedangkan, pendidikan akhlak yang terkandung di dalamnya adalah gotong royong (ta’awun), menghormati tamu (ikram dhuyuf), dan kebersamaan (ma’iyah).